2017
DOI: 10.3390/biom7010002
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin-Based Blood Substitutes and the Treatment of Sickle Cell Disease: More Harm than Help?

Abstract: Intense efforts have been made by both industry and academia over the last three decades to produce viable hemoglobin (Hb)-based oxygen carriers (HBOCs), also known as “blood substitutes”. Human trials conducted so far by several manufactures in a variety of clinical indications, including trauma, and elective surgeries have failed and no product has gained the Food and Drug Administration approval for human use. Safety concerns due to frequent incidences of hemodynamic, cardiac events, and even death led to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 82 publications
(95 reference statements)
0
46
0
Order By: Relevance
“…13 However, other studies suggested a potential renal toxicity of polymerized Hb systems associated with oxidative stress. 14,15 Despite great efforts and recent progress for the development of new blood substitutes, no HBOCs have yet been approved for clinical use in Europe or in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, other studies suggested a potential renal toxicity of polymerized Hb systems associated with oxidative stress. 14,15 Despite great efforts and recent progress for the development of new blood substitutes, no HBOCs have yet been approved for clinical use in Europe or in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin‐based oxygen carriers (HBOCs) are blood substitutes derived from bovine, pig, or outdated human blood . The potential benefits of HBOCs include universal compatibility without the need for cross‐matching of donated blood, availability, and no infection risks .…”
mentioning
confidence: 99%
“…Physicians are faced with a significant challenge when treating life-threatening anemia in patients unwilling to accept blood for religious reasons or for whom safe blood is not available due to extensive alloimmunization or lack of supply in some developing countries. 3,6,[15][16][17][18][19] Unfortunately, survival of patients with life-threatening anemia for whom RBC transfusion is not an option has not improved over the past 20 or 30 years. 20,21 Administration of HBOCs may represent a therapeutic alternative to reduce mortality for both medical and surgical patients in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where hemoglobin (Hb) levels are insufficient to fulfill metabolic needs, red blood cell (RBC) and exchange transfusion are often utilized. However, Jehovah's Witnesses (JWs) typically refuse blood products or compatible RBCs may not be available or safe . Cell‐free Hb substitutes have improved over the past 30 years, with significant improvements in the safety profiles and clinical outcomes of second‐generation Hb‐based oxygen carriers (HBOCs) .…”
mentioning
confidence: 99%
See 1 more Smart Citation